Índice neutrófilos/linfocitos y mortalidad en pacientes con pancreatitis aguda atendidos en el Hospital Regional Docente de Trujillo en los años 2017 y 2018 - Diaz Núñez, Pierina Lucimar (2021)
To determine the relationship between the neutrophil/lymphocyte ratio (NLR) and mortality in patients with acute pancreatitis (AP). MATERIAL AND METHOD: Observational, retrospective and transversal study. Medical records of patients diagnosed with AP, admitted to the Trujillo Regional Teaching Hospital in the years 2017 and 2018, were reviewed. Patients were classified by their mortality according to BISAP, and their NLR was calculated in emergency admission. The ROC curve was plotted. RESULTS: 89% of the patients (n=113) had lower mortality according to BISAP and only 11% (n=13) showed higher mortality. The mean NLR was 6.26 (SD ± 3.20). The NLR cut-off point was 7.38, with a sensitivity of 100%, specificity of 85%, PPV of 43%, NPV of 100% and area under the curve of 0.96 (95% CI: 0.92-0.99). CONCLUSION: There is a statistically significant association between the NLR value and AP mortality.